Tonsillar Application of Formalin-Killed Cells of Streptococcus sobrinus Reduces Experimental Dental Caries in Rabbits - Fukuizumi, Takaki (American Society for Microbiology, 1999)
Living Streptococcus sobrinus cells were orally inoculated into nonimmune rabbits and rabbits immunized with formalin-killed cells of S. sobrinus through tonsillar application to examine the anticaries potential of this method of immunization. The living S. sobrinus cell numbers and the caries areas in the rabbits immunized by tonsillar application decreased to a level one-fifth of that in nonimmune rabbits.